Permeable Personhood and Techniques for Negotiating Boundaries of the Self among the Luangans of Indonesian Borneo - Herrmans, Isabell (Asiatische Studien - Études Asiatiques, 2017)
This article explores the negotiation of permeable personhood and human health and well-being in the healing rituals (belian) of the Luangans, a group of indigenous people of Indonesian Borneo. I describe different techniques employed in the rituals relating to the soul and other components of the self and to extraneous, unbound spirit agencies. Luangan rituals express a relational ontology according to which the constitution of personhood and human well-being is based on the condition of the notoriously volatile human soul or life-force (juus) and the nature of social relations with human and nonhuman beings. Rituals most centrally seek to advance well-being by increasing the fixity and hardness of souls and by improving the relationship with spirits and humans. These efforts are closely interconnected; the condition of the soul is inextricably bound up with the condition of relations with others. This entails a constitutively dual and contextually variable aspiration to both reinforce and open up the boundaries of persons and to associate and dissociate with others. While well-being is generally contingent on containing the soul within the body and alleviating the harmful influence on it of spirits and other humans, it is also adversely affected by alienation and neglect of relations and obligations, and dependent on the help of spirits and human shamans and consociates. The article describes the ambiguous and convoluted nature of Luangan human-spirit relations and how the unpredictability of these relations and the volatility of the soul is reflected in the structure of ritual performances. <br